2009
DOI: 10.17221/621-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Content of Higher Fatty Acids in Green Vegetables

Abstract: Green vegetables are considered an important source of some nutritionally important constituents that have health benefits (e.g. vitamins, minerals, antioxidants, fibre). Epidemiological data suggest that consuming a diet rich in fruit and vegetables can lower the risks for chronic diseases, such as cardiovascular diseases and cancer. Over the past 100–150 years, there have been enormous increases in the consumption of omega-6 fatty acids due to the increased intake of vegetable oils from various seeds. Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Rennie and Tanner (1991) reported the presence of palmitoleic acid in soybean leaf oil, while Artichoke (2.3%) and Kale (3.2%) leaves were reported to contain higher amounts of palmitoleic acid (Vidrih et al, 2009) than the contents of D. repens presented in this study. Oyster mushroom oil and Radish leaf oil according to the reports of Vidrih et al (2009) recorded a comparable oleic acid composition to that of D. repens leaf oil presented in this study while the linoleic acid composition (46.92%); being the highest amount of constituent fatty acid in the D. repens leaf oil evaluated in this study, was comparable to oils from Alfalfa sprouts (44.1%), Parsley leaf (44.8%) and red bell pepper (41.4%) but higher than oils from eggplant, cucumber, red cabbage and lettuce (Vidrih et al, 2009). It is well documented that both monounsaturated fatty acids and polyunsaturated fatty acids induce elevated levels of HDL and reduce LDL levels (FAO/WHO, 2010).…”
Section: Resultsmentioning
confidence: 45%
“…Rennie and Tanner (1991) reported the presence of palmitoleic acid in soybean leaf oil, while Artichoke (2.3%) and Kale (3.2%) leaves were reported to contain higher amounts of palmitoleic acid (Vidrih et al, 2009) than the contents of D. repens presented in this study. Oyster mushroom oil and Radish leaf oil according to the reports of Vidrih et al (2009) recorded a comparable oleic acid composition to that of D. repens leaf oil presented in this study while the linoleic acid composition (46.92%); being the highest amount of constituent fatty acid in the D. repens leaf oil evaluated in this study, was comparable to oils from Alfalfa sprouts (44.1%), Parsley leaf (44.8%) and red bell pepper (41.4%) but higher than oils from eggplant, cucumber, red cabbage and lettuce (Vidrih et al, 2009). It is well documented that both monounsaturated fatty acids and polyunsaturated fatty acids induce elevated levels of HDL and reduce LDL levels (FAO/WHO, 2010).…”
Section: Resultsmentioning
confidence: 45%
“…There are several reports having fatty acid composition in seeds as well as vegetative parts of several Brassica crops (Velasco et al, 1998;West et al, 2002;Matthaus et al, 2003;Barthet, 2008;Vidrih et al, 2009), however information regarding fatty acid composition in broccoli is limited. Although, fatty acid composition in floret part of broccoli has been studied (West et al, 2002;Vidrih et al, 2009), only one cultivar was selected and the name was not clearly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Although, fatty acid composition in floret part of broccoli has been studied (West et al, 2002;Vidrih et al, 2009), only one cultivar was selected and the name was not clearly identified. Furthermore, regarding the fatty acid composition in leaves and stem parts, there are no official data available.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the leaves are the superior source of ALA and PUFA compared to seeds, flowers and tender pods [8,20], and can be used as a significant source of ALA. With regard to health benefits, M. oleifera leaves contain a low amount of SFA and a high mono-and polyunsaturated fatty acid content, which can enhance the health benefits of Moringa-based products. Green leafy vegetables have been established as a potential source of ALA-Vidrih et al [21] recorded C50 % of ALA in fatty acids extracted from tarragon (Artemisia dracunculus), green lettuce, zucchini (Cucurbita pepo), and broccoli.…”
Section: Resultsmentioning
confidence: 99%